Binary Quasi-differential Stochastic Process Keying Modulation Scheme for Covert Communications - Z. J. Xu; S. Zhang; Z. W. Liu; J. L. Lin; X. S. Huang; Y. Gong (Radioengineering)
Covert communication working at the physical layer provides an important means for ensuring the security of private user data. This work proposes a novel covert communication system based on binary quasi-differential stochastic process keying (BQDSPK). At the transmitter, the polarity of the correlation coefficient of two consecutive stochastic sequences is modulated by one binary covert bit. At the receiver, the correlation between two consecutively received random sequences is computed, and the transmitted covert bit is inferred through a hard decision process. A pseudo-random sequence is introduced to eliminate the transmitted sequences' correlation. The transmitted signal has the same statistical characteristics as the ambient noise to avoid attracting the attention of eavesdroppers. We theoretically demonstrate that the proposed system fully satisfies the requirement of covert communication when the signal-to-noise ratio (SNR) is less than a certain threshold value. In addition, theoretical bit error rate (BER) expressions are derived under additive white Gaussian noise (AWGN) channels and frequency-flat fading channels. The simulation results show that the theoretical BERs are very close to the BERs obtained from the simulations, regardless of which stochastic process is used as the carrier. Specifically, when the number of samples within a bit period is 400, the BER approaches approximately 10^-5 at a SNR of -5 dB under an AWGN channel, which adequately satisfies the communication requirements.